Perancangan Meja Kerja Penempatan Rapat dengan Metode Optimasi Utilitas Luas Permukaan - Ilyas Mas'udin (Jurnal Teknik Industri, 2000)
Placing same different I various dimension (length and width ) problem  on work station to process at a machine is a similar problem with "pallet  loading"  .A had placing method cause low utility of table are or low prosentage  of used table area.  If every process had fixed cost, so it causer hight production  cost per unit.That's why we need a good part placing  method to optimaize table usa.  This research  had optimaized wark table  method with  different parts of sizes using dynamic programes   upproching. The model made only considering length and width demansion of each part .